Cidadania contra a democracia: as contradições comunicacionais dos movimentos sociais no Brasil, de Dilma Rousseff a Jair Bolsonaro - Signates, Luiz; Leal, Maiara Raquel Campos (Brasiliana: Journal for Brazilian Studies, 2021)
The general objective of the article is to explore some communicational contradictions of the conservative social movements that acted in Brazil in the last decade, more specifically, between Dilma Rousseff's second term in office until the second year of Jair Bolsonaro's current government (2015-2020), also situating how the particularities of political culture in the country are reflected in the conflicting relationship between citizenship and democracy, which has worsened in the pandemic context, mainly by the influence of social networks. We seek to delineate the communicational meanings that were unleashed by these collectives and activisms during the period, as they represent the communicational devices of struggle for legitimization within the democratic condition. We conclude by stating that Brazilian democracy is not yet a citizen experience, or that Brazilian citizenship is not a democratic experience, mainly due to the lack of communicability in the ties that unite the two conditions in the social experience of the population.